Burden of bacterial bloodstream infection—a brief update on epidemiology and significance of multidrug-resistant pathogens. (February 2020) - Kern, W.V.; Rieg, S.
Abstract: Background: Bloodstream infections comprise a wide variety of pathogens and clinical syndromes with considerable overlap with similar syndromes of non-bacteraemic infections and diverse risk factors, therapeutic implications and outcomes. Yet, this heterogeneous 'entity' has the advantage to be pathogen-defined compared with the broad and even more heterogeneous entity 'sepsis', and so has become helpful for clinicians and epidemiologists for research and surveillance purposes. The increasing availability of population-based and large multicentre well-defined cohort studies should allow us to assess with much confidence and in detail its burden, the significance of antimicrobial resistance, and areas of uncertainty regarding further epidemiological evolution and optimized treatment regimens. Aim: To review key aspects of bloodstream infection epidemiology and burden, and summarize recent news and questions concerning critical developments. Sources: Peer-reviewed articles based on the search terms 'bloodstream infection' and 'bacteremia' combined with the terms 'epidemiology' and 'burden'. The emphasis was on new information from studies in adult patients and on the added burden due to pathogen resistance to first- and second-line antimicrobial agents. Content: Topics covered include recent developments in the epidemiology of bloodstream infection due to key pathogens and published information about the relevance of resistance for patient outcomes. Implications: Despite the availability of population-based studies and an increasing number of large well-defined multicentre cohort studies, more surveillance and systematic data on bloodstream infection epidemiology at regional level and in resource-limited settings may be needed to better design new methods for prevention and define the need for and further develop optimized therapeutic strategies.